2021
DOI: 10.1097/md.0000000000027668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhalation and propofol anaesthesia on postoperative cognitive dysfunction in elderly noncardiac surgical patients

Abstract: Background: Postoperative cognitive dysfunction (POCD) is a very common event in elderly noncardiac surgical patients. The effects of inhalational anaesthetics and propofol on the incidence of POCD and postoperative cognitive status at different time points after surgery are currently unclear.Methods: We searched the Embase, Medline, Cochrane Library, and Web of Science databases for randomized controlled trials (RCTs), in which inhalation anaesthesia and propofol anaesthesia were compared. The incidence of PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
(139 reference statements)
0
11
0
1
Order By: Relevance
“…Preoperative MMSE scores were comparable between groups (27 [26][27][28][29] in group D and 27.5 [26][27][28] in group P; p = 0.514). There were no significant differences in MMSE scores at the four evaluation time points.…”
Section: Primary Outcomementioning
confidence: 87%
“…Preoperative MMSE scores were comparable between groups (27 [26][27][28][29] in group D and 27.5 [26][27][28] in group P; p = 0.514). There were no significant differences in MMSE scores at the four evaluation time points.…”
Section: Primary Outcomementioning
confidence: 87%
“…In addition, we reported that TNF-αinduced accumulation of p-Tau was attenuated by propofol pretreatment (Figure 2(a)), and one of the astonishing findings of our study is that propofol, within clinically achieved concentrations, may reduce the basic level of p-Tau (Figure 2(b)). Although whether propofol exerts beneficial or detrimental effects to CNS in the clinical practice is debatable [29][30][31], a large body of in vitro evidence from us and other researchers proved the anti-inflammation and neuro-protective property of propofol [16][17][18][19]. The current findings implied a novel research field to the neuroprotective effect of propofol and more importantly provided a novel target for the protection of neurons and neurodegenerative disorders against inflammation.…”
Section: Discussionmentioning
confidence: 62%
“…Those children require continuous follow up. Furthermore, though recent study on 7-11 years old children who were conducted general anesthesia under 3 has shown that the exposure to general anesthesia in early childhood was not markedly related to the reduced intelligence in later stage (Schuttler et al, 2021), anesthesia was still demonstrated to be a non-negligible factor of cognitive levels in many studies (Pang et al, 2021;Shen et al, 2021;Wu and Zhu, 2021). However, we did not analyze the effect of anesthesia on cognition because of lots of anesthesia data missed.…”
Section: Resultsmentioning
confidence: 95%